anonymous
  • anonymous
What is the value of x? −x = 6 − 4x + 18
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
schrodinger
  • schrodinger
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
I think it is -8
anonymous
  • anonymous
Close, but it would be x=8.
anonymous
  • anonymous
I think you just got a negative mixed up somewhere.

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
Let's solve your equation step-by-step. −x=6−4x+18 Step 1: Simplify both sides of the equation. −x=6−4x+18 Simplify: (Show steps) −x=−4x+24 Step 2: Add 4x to both sides. −x+4x=−4x+24+4x 3x=24 Step 3: Divide both sides by 3. 3x/3=24/3 x=8 Answer: x=8
anonymous
  • anonymous
here you go Simplifying 2x + 6 = 4x + -2 Reorder the terms: 6 + 2x = 4x + -2 Reorder the terms: 6 + 2x = -2 + 4x Solving 6 + 2x = -2 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 6 + 2x + -4x = -2 + 4x + -4x Combine like terms: 2x + -4x = -2x 6 + -2x = -2 + 4x + -4x Combine like terms: 4x + -4x = 0 6 + -2x = -2 + 0 6 + -2x = -2 Add '-6' to each side of the equation. 6 + -6 + -2x = -2 + -6 Combine like terms: 6 + -6 = 0 0 + -2x = -2 + -6 -2x = -2 + -6 Combine like terms: -2 + -6 = -8 -2x = -8 Divide each side by '-2'. x = 4 Simplifying x = 4
anonymous
  • anonymous
x=8 not x=-8

Looking for something else?

Not the answer you are looking for? Search for more explanations.